Development of problem-based learning mathematics tools for linear programming to facilitate students' mathematical communication skills - Yeyen, Vioskha; Roza, Yenita; Murni, Atma (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This research is driven by the challenges teachers face in designing learning tools aligned with the 2013 curriculum. The purpose of this study is to develop mathematics learning tools based on the Problem-Based Learning (PBL) model to enhance students' mathematical communication skills, ensuring these tools are both valid and practical. The developed learning tools include a syllabus, Lesson Plan, and Student Worksheets. The development process follows the 4-D model, which consists of the stages: Define, Design, Develop, and Disseminate. The subjects of this study were 35 students from class XI at SMAN 5 Tapung. Research instruments included validation sheets to assess the feasibility and validity of the learning tools and student response questionnaires to evaluate the practicality of the student worksheets. The analysis of validation data revealed that the mathematics learning tools are highly valid, with an average rating of 94% for the syllabus, 95% for the lesson plan, and 92% for the student worksheets. The practicality data analysis showed that the student response ratings categorized the tools as very practical, with an average rating of 88.37%.